Essence of Indecision : Diefenbaker's Nuclear Policy, 1957-1963 - McMahon, Patricia I., 1972- (McGill-Queen's University Press, 2009)
The nuclear issue was a minor political matter when John Diefenbaker became prime minister in 1957. By 1963, it served as a catalyst for his defeat, with many attributing his demise to the indecision with which he handled it. Patricia McMahon tells a more nuanced story in Essence of Indecision.